Risk factors for ulcerative colitis-associated colorectal cancer: A retrospective cohort study. Issue 32 (7th August 2020) - de Campos Silva, Elen Farinelli; Baima, Julio Pinheiro; de Barros, Jaqueline Ribeiro; Tanni, Suzana Erico; Schreck, Thomas; Saad-Hossne, Rogerio; Sassaki, Ligia Yukie
Abstract : Abstract: Inflammatory bowel disease is associated with an increased risk of colorectal cancer. The study aims to identify the risk factors for ulcerative colitis-colorectal cancer and to perform a survival curve analysis of the outcome. This retrospective cohort study included 254 patients from March 2016 to October 2017. Age, age at diagnosis, follow-up time, smoking status, and family history of colorectal cancer were analyzed as risk factors for colorectal cancer. The mean patient age was 46.6 ± 16.9 years; 5.5% of the patients were smokers and 49.6% had pancolitis. Six patients (2.36%) had colorectal cancer, which was associated with age at diagnosis (odds/hazard ratio 1.059 [95% confidence interval: 1.001–1.121]; P  = .04), family history of colorectal cancer (12.992 [1.611–104.7]; P  = .02), and follow-up time (0.665 [0.513–0.864]; P  = .002). Active smoking was the main identified risk factor, after both logistic (8.477 [1.350–53.232]; P  = .02) and Cox proportional-hazards (32.484 [2.465–428.1]; P  = .008) regression analysis. The risk of colorectal cancer was 3.17% at 10 years and 4.26% at 20 years of follow-up. Active smoking and family history were identified as risk factors for colorectal cancer. These findings should aid the early identification of patients who require vigorous surveillance, and prevent exposure to risk factors.